1990
DOI: 10.1159/000125588
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of 5-Alpha-Dihydroprogesterone on Nuclear Estrogen Receptor Binding of the Anterior Pituitary and Uterus in the Rat

Abstract: Progesterone and its metabolite 5α-dihydroprogesterone (5α-DHP) have been shown to bring about gonadotropin release in the estrogen-primed ovariectomized rat. One of the actions of progesterone is the decrease in occupied estrogen receptors (E2RS) in the anterior pituitary and uterus. This study attempted to determine if 5α-DHP had a similar effect on pituitary and uterine E2RS. Estrogen-primed ovariectomized mature female rats were injected with either vehicle, or 0.2, 0.8 or 2 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In that study there appeared to be no changes in -actin mRNA levels at different times after estradiol administration, and the results were similar whether they were corrected using -actin or uncorrected for variations in transfer. Other tissue-specific differences in ER dynamics between the pituitary and the uterus have been reported by us earlier using progesterone [11,46], 5oL-pregnane-3,20-dione [22], and a5o-dihydrotestosterone and dexamethasone [16]. Furthermore, in the present study, ER mRNA levels in the uterus were increased after ovariectomy and decreased after estrogen priming, whereas in the anterior pituitary ER mRNA levels are decreased after ovariectomy and increased after estrogen priming [45].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In that study there appeared to be no changes in -actin mRNA levels at different times after estradiol administration, and the results were similar whether they were corrected using -actin or uncorrected for variations in transfer. Other tissue-specific differences in ER dynamics between the pituitary and the uterus have been reported by us earlier using progesterone [11,46], 5oL-pregnane-3,20-dione [22], and a5o-dihydrotestosterone and dexamethasone [16]. Furthermore, in the present study, ER mRNA levels in the uterus were increased after ovariectomy and decreased after estrogen priming, whereas in the anterior pituitary ER mRNA levels are decreased after ovariectomy and increased after estrogen priming [45].…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies from our laboratory have demonstrated a dose-dependent decrease in occupied nuclear uterine ER in estrogen-primed, ovariectomized rats treated with either progesterone or 5a-dihydroprogesterone [11,22]. Dramatic decreases in uterine ER binding have also been observed after a single injection of estradiol by several investigators who have shown replenishment of the binding activity in 16-24 h [3, 6, 7, 23-25].…”
Section: Discussionmentioning
confidence: 91%
“…In view of the uniqueness of these multiphasic actions of progesterone and differences in progesterone effects on E,R binding in the pituitary and the uterus, the studies were repeated using 5a-dihydroprogesterone, a metabolite of progesterone that utilizes the progesterone receptor (3 1). The pattern of effects of progesterone and Sa-dihydroprogesterone on pituitary and uterine E,R binding were similar (31).…”
Section: Discussionmentioning
confidence: 71%
“…similar to effects of progesterone (104). The role(s) of 5a-DHP and AR in regulation of ovine endometrial physiology remains unknown.…”
Section: Pregnancy Recognition In Ruminants 225mentioning
confidence: 99%